DETERMINATION OF THE COMBINED WIDTH OF MAXILLARY ANTERIOR TEETH USING INNERCANTHAL DISTANCE WITH RESPECT TO AGE GENDER AND ETHINICITY - Naseer Ahmed (Army Medical College Rawalpindi, 2021)
Objective: To evaluate the relationship between inner canthal distance and maxillary anterior teeth width with respect to age, gender and ethnicity.